Foot-and-mouth disease virus non-structural protein 2B downregulates the RLR signaling pathway via degradation of RIG-I and MDA5 - Weerawardhana, Asela; Uddin, Md Bashir; Choi, Joo-Hyung; Pathinayake, Prabuddha; Shin, Sung Ho; Chathuranga, Kiramage; Park, Jong-Hyeon; Lee, Jong-Soo (Frontiers in Immunology, 2022)
Foot-and-mouth disease virus (FMDV) is a single-stranded, positive-sense RNA virus containing at least 13 proteins. Many of these proteins show immune modulation capabilities. As a non-structural protein of the FMDV, 2B is involved in the rearrangement of the host cell membranes and the disruption of the host secretory pathway as a viroporin. Previous studies have also shown that FMDV 2B plays a role in the modulation of host type-I interferon (IFN) responses through the inhibition of expression of RIG-I and MDA5, key cytosolic sensors of the type-I IFN signaling. However, the exact molecular mechanism is poorly understood. Here, we demonstrated that FMDV 2B modulates host IFN signal pathway by the degradation of RIG-I and MDA5. FMDV 2B targeted the RIG-I for ubiquitination and proteasomal degradation by recruiting E3 ubiquitin ligase ring finger protein 125 (RNF125) and also targeted MDA5 for apoptosis-induced caspase-3- and caspase-8-dependent degradation. Ultimately, FMDV 2B significantly inhibited RNA virus-induced IFN-β production. Importantly, we identified that the C-terminal amino acids 126-154 of FMDV 2B are essential for 2B-mediated degradation of the RIG-I and MDA5. Collectively, these results provide a clearer understanding of the specific molecular mechanisms used by FMDV 2B to inhibit the IFN responses and a rational approach to virus attenuation for future vaccine development.